The Past is a Foreign Country: Revisited - Lowenthal, David (New York Cambridge University Press, 2015)
The past remains essential - and inescapable. A quarter-century after the publication of his classic account of man's attitudes to his past, David Lowenthal revisits how we celebrate, expunge, contest and domesticate the past to serve present needs. He shows how nostalgia and heritage now pervade every facet of public and popular culture. History embraces nature and the cosmos as well as humanity. The past is seen and touched and tasted and smelt as well as heard and read about. Empathy, re-enactment, memory and commemoration overwhelm traditional history. A unified past once certified by experts and reliant on written texts has become a fragmented, contested history forged by us all. New insights into history and memory, bias and objectivity, artefacts and monuments, identity and authenticity, and remorse and contrition, make this book once again the essential guide to the past that we inherit, reshape and bequeath to the future.
Keywords: Past; Philosophy; History